A study on relationship between work stress and employee performance in CTRM Aero Composites (CTRM AC) at Composites Technology City in Batu Berendam, Melaka / Rugayah Ab Rashid and Wan Hazwani Wan Halimi - Ab Rashid, Rugayah; Wan Halimi, Wan Hazwani (2014)
Organization nowadays are facing common problem, which is work stress among their employees. In this study, the researcher choose to study whether work stress factor affect employee performance at CTRM Aero Composites Sdn Bhd, Batu Berendam, Melaka. Work stress can be define as harmful physical and emotional responses that occur when the requirements of a job match the capabilities, resources or needs of the worker. Work or stress can result to poor performance, which the management should be aware of the factors and manage or reduce them to avoid loss in the organization. This study consist of the analysis on the relationship between work stress factors with employee performance. The factors are work load, role conflict and work environment. Data were collected from questionnaires answered by employees from Value Stream 2, CTRM AC, with total respondents of 140. The data then were processed using Statistical Package for Social Science (SPSS) program version 20.0. The data were intepreted in Frequencies Analysis, Reliability Test, Descriptive Analysis, Correlation Analysis and Regression Analysis. The results show that there are relationship between work stress factors with employee performance. The most influential factor was work environment. This study is beneficial to the organization as the management can have the information about what are the major factor that contribute to work stress among their employees. With that, they can do further actions that are necessary to overcome this situation in order to ensure organization’s effectiveness. Some of the actions were also recommended by the researcher in this study. Future study should focus on similar factor but must be expanded to other division or other organizations. With that, we can get a clear picture on work stress among employees in any industry.